2023
DOI: 10.1002/mame.202300003
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion Improvement of Bio‐Based Epoxy in Environmentally Friendly and High‐Performance Natural Fiber‐Reinforced Composites

Abstract: Developing robust bio‐based epoxy against petroleum‐derived epoxy is necessary for environmentally friendly and high‐performance natural fiber‐reinforced composites. A bio‐based vanillin epoxy (VE) is synthesized from the lignin‐derived vanillin, and a thermoset resin is prepared after mixing it with a 4,4′‐diaminodiphenyl methane (DDM) hardener. Further, it is infused in high‐cellulose‐containing alkali‐treated jute fiber (TJF) mats through a simple approach to enhance the adhesion between the VE‐DDM and TJF.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 59 publications
(375 reference statements)
0
7
0
Order By: Relevance
“…However, the absorption bands of the epoxy ring in the cured VE-DDM thermoset were consumed entirely after curing with the hardener. A new absorption band for the C N bond at 1620 cm −1 is due to the reaction between the formyl (-CH O) group of VE and the –NH 2 group of hardener [ 30 , 31 ]. Another noticeable change is the decrease in the band intensity of the formyl group after the curing, suggesting the successful completion of the curing between the epoxy and the hardener.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the absorption bands of the epoxy ring in the cured VE-DDM thermoset were consumed entirely after curing with the hardener. A new absorption band for the C N bond at 1620 cm −1 is due to the reaction between the formyl (-CH O) group of VE and the –NH 2 group of hardener [ 30 , 31 ]. Another noticeable change is the decrease in the band intensity of the formyl group after the curing, suggesting the successful completion of the curing between the epoxy and the hardener.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, the VE-DDM resin showed good interfacial adhesion around 13.93 ± 0.26 MPa with CNF film ( Fig. S7 ) because of its excellent compatibility and crosslinking [ 31 ]. The underlying mechanisms for the increased mechanical properties are etherification and crosslinked network structure.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, traditional polyimides mostly originate from fossil raw materials, which not only cause environmental pollution and fossil fuel consumption but also may pose a carcinogenic risk to experimental personnel. In the current "dual carbon" context, it is particularly important to develop bio-based polyimides with raw materials partly or wholly derived from biomass [29][30][31]. At present, bio-based polyimides are limited to adding bio-based content, which is far from the early goal of complete substitution.…”
Section: Introductionmentioning
confidence: 99%